Finding Sound Absorption Coefficients On Porous Absorber Material by Using COMSOL Simulation and Impedance Tube Method - ISMAIL, MUHAMMAD IFFZAN IMAN; MD ARIFFIN, LATIFAH (Research Progress in Mechanical and Manufacturing Engineering, 2022)
There are several methods in finding the best sound absorption coefficient on three types of most common porous absorber. The aim of this study is to conduct modelling of material sample on COMSOL Multiphysics to find the best sound absorption coefficient among the materials and the resulted sound absorption coefficient will be compared based on both methods used. The porous materials including melamine foam, wood wool cement board, glass fibre which will be tested on COMSOL Multiphysics and Impedance Tube. Noise Reduction Coefficient will be included in determining the best material that have the best sound absorption. Melamine foam has the best sound absorption properties based on the calculate NRC and there are slight inaccuracy in COMSOL Simulation which need to develop for future use.